Sequence determinants of the conformational properties of an intrinsically disordered protein prior to and upon multisite phosphorylation - Martin, Erik W. (J Am Chem Soc, 2016)
Many cell signaling events are coordinated by intrinsically disordered protein regions (IDRs) that undergo multisite Serine/Threonine phosphorylation. The conformational properties of these IDRs prior to and following multi-site phosphorylation are directly relevant to understanding their functions. Here, we present results from biophysical studies and molecular simulations that quantify the conformational properties of an 81-residue IDR from the S. cerevisiae transcription factor Ash1. We show that the unphosphorylated Ash1 IDR adopts coil-like conformations that are expanded and well-solvated. This result contradicts inferences regarding global compaction that are derived from heuristics based on amino acid compositions for IDRs with low proline contents. Upon phosphorylation at ten distinct sites, the global conformational properties of pAsh1 are indistinguishable from those of unphosphorylated Ash1. This insensitivity derives from compensatory changes to the pattern of local and long-range intra-chain contacts. We show that the conformational properties of Ash1 and pAsh1 can be explained in terms of the linear sequence patterning of proline and charged residues vis-à-vis all other residues. The sequence features of the Ash1 IDR are shared by many other IDRs that undergo multisite phosphorylation. Accordingly, we propose that our findings might be generalizable to other IDRs involved in cell signaling.